Estudo Do Índice De Adiposidade Corporal Em Idosos Longevos Independentes - Spinoza, Evelyn Dearo [UNIFESP] (2018)
Objective: To Verify The Validity Of The Body Adiposity Index (Bai) As A Predictor Of Body Fat In Older And Independent Brazilian Elderly. Type Of Study: Transversal. Methods: Serum Creatinine Level And Anthropometric Measurements (Weight, Height, Hip Circumference) Were Performed. Dual-Energy X-Ray Absorptiometry (Dxa) Was Used To Calculate The Percentage Of Body Fat Which Was Compared With Bai And Body Mass Index (Bmi). We Performed The Pearson Correlations And To Compare The Reliability Between The Methods, We Used The Alpha Of Bland And Altman Cronbach. Results: A Total Of 157 Individuals (Mean Age 87 Years Old, ±3.57) Were Evaluated. The Correlation Of Bai With Dexa Was Moderate (R = 0.59 For Men And R = 0.67 For Women, P <0.001). Reliability Was Confirmed By Cronbach's Alpha With 0.67 For Men And 0.77 For Women. Conclusion: Bai May Be An Alternative Method For Assessing Body Fat In The Independent Oldest Old People.